The effectiveness of blended learning on critical thinking skills among secondary school students in chemistry subject - Almarzuqi, Ali Abdullah; Sulaiman, Tajularipin; Mustakim, Siti Salina (Human Resources Management Academic Research Society (HRMARS), 2024)
This study examines the efficacy of blended learning in improving critical thinking abilities in chemistry among secondary school pupils. Blended learning combines traditional in-person teaching with online learning methods, creating an interactive educational approach that encourages active participation, collaborative problem-solving, and self-awareness. This study does a thorough analysis of contemporary academic literature to explore how blended learning impacts critical thinking abilities by examining theoretical frameworks such as constructivism, social cognitive theory, and cognitive load theory. The synthesis and analysis of empirical research investigate the effects of blended learning interventions on students' capacity to interpret chemical ideas, assess experimental data, and make informed judgments. Furthermore, this article examines the many elements that impact the efficacy of blended learning, such as instructional design, technology infrastructure, teacher support, and student motivation. Through the utilization of blended learning and the incorporation of evidence-based teaching methodologies, educators have the ability to enable secondary school students to engage in critical thinking, creative problem-solving, and successful application of their knowledge in the field of chemistry. This paper's findings add to the expanding body of knowledge on blended learning and offer valuable insights for educators, policymakers, and researchers who aim to improve student learning outcomes in secondary school chemistry instruction